2016
DOI: 10.3390/w8010019
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Temporal Changes of Model Parameters in Rainfall-Runoff Modeling via a Real-Time Data Assimilation

Abstract: Abstract:Watershed characteristics such as patterns of land use and land cover (LULC), soil structure and river systems, have substantially changed due to natural and anthropogenic factors. To adapt hydrological models to the changing characteristics of watersheds, one of the feasible strategies is to explicitly estimate the changed parameters. However, few approaches have been dedicated to these non-stationary conditions. In this study, we employ an ensemble Kalman filter (EnKF) technique with a constrained p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…However, it is no longer appropriate to use constant parameters, especially for hydrological modeling under the changing environment. A temporal variability of the model parameters exists due to the influence of catchment condition changes including climate condition and catchment characteristics (e.g., land use and land cover) [12][13][14][15][16]. For example, Wang and Tang [17] found that rainfall and vegetation were the dominant controlling factors on the parameter of a Budyko equation, which is derived for mean annual water balance and is independent of temporal scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is no longer appropriate to use constant parameters, especially for hydrological modeling under the changing environment. A temporal variability of the model parameters exists due to the influence of catchment condition changes including climate condition and catchment characteristics (e.g., land use and land cover) [12][13][14][15][16]. For example, Wang and Tang [17] found that rainfall and vegetation were the dominant controlling factors on the parameter of a Budyko equation, which is derived for mean annual water balance and is independent of temporal scale.…”
Section: Introductionmentioning
confidence: 99%
“…The first is to calibrate parameters in consecutive subsets of the historical data and attempts to obtain their values separately in each period using optimization algorithms [20,21]. The second method is to estimate model parameters via data assimilation techniques based on the available observations [12,15]. Another method of estimating time-variant parameters is to establish the parameter functions as dependent on covariates that can reflect the variability of catchment conditions [22].…”
Section: Introductionmentioning
confidence: 99%
“…The Xinanjiang (XAJ) model, a rainfall-runoff model developed by (Zhao 1992), has been widely used in China and many countries in the world for flood simulation in humid and semi-humid regions (Huo and Liu 2020;Liu et al 2016;Meng et al 2016;Yang et al 2020;Zhang et al 2019;Zhuo et al 2016). It is based on the concept of saturation excess runoff mechanism, which means that runoff is not produced until the soil moisture content of the aeration zone reaches field capacity.…”
Section: Xinanjiang Modelmentioning
confidence: 99%
“…The generated runoff is divided into the surface flow, interflow, and groundwater using steady infiltration. The total runoff can be routed by a linear system before arriving at the outlet of the catchment [37]. Flow routing uses the Muskingum or piecewise continuous algorithm.…”
Section: Precipitation-runoffmentioning
confidence: 99%